Pediatric Renal Admission: Clinical Spectrum and Outcome, the Experience of Two Semi-urban, Secondary Hospitals in Cameroon - Teuwafeu, Denis Georges; Mambap, Alex; Foin, Frank; Puepi, Yolande; Gobina , Ronald; Ashuntantang, Gloria (Journal of Pediatric Nephrology, 2022)
Background and aim: There is limited data on renal diseases in paediatric admissions in Cameroon. The aim was to describe the clinical spectrum and outcomes of renal diseases among admitted children in two regional hospitals in Cameroon. Materials and Methods: we reviewed archived records of children admitted with renal disease from the 1st January 2017 to 31st December 2019 for renal diseases and outcomes. Results: In all, 148 (1.98%) of the 7457 admitted children had a renal disease. Their median age was 7.5 years (IQR 4-12) and 63.5% were females with 32.4% less than 5years. Urinary tract infection (51.4%), Acute kidney injury (21.6%), Nephrotic syndrome (12.2%), chronic kidney disease (12.2%) and renal mass (2.6%) were frequently described. Complicated UTI was observed in 9.2% of children with UTI whereas initiation of corticotherapy (83.3%) was the most common reason for admission in children with nephrotic syndrome. Malaria (40.6%) and sepsis (40.6%) were the most common aetiology of AKI whereas chronic GN was the most common aetiology of CKD. Out of the 32 children with AKI, 50% had an indication for dialysis with 87.5% having access to the therapy. Nine (75%) of the 12 children with non-dialysed CKD-5 needed dialysis with 55.5% (5/9) having access to it. Out of the 148 children, 07 (4.7%) died. Deaths were due to AKI and CKD; with specific death rates of 12.5% and 16.7% respectively. Conclusion: Renal diseases are uncommon among admitted children. Overall in-hospital mortality was low.